2017
DOI: 10.1111/tpj.13774
|View full text |Cite
|
Sign up to set email alerts
|

Apple fruit superficial scald resistance mediated by ethylene inhibition is associated with diverse metabolic processes

Abstract: Fruits stored at low temperature can exhibit different types of chilling injury. In apple, one of the most serious physiological disorders is superficial scald, which is characterized by discoloration and brown necrotic patches on the fruit exocarp. Although this phenomenon is widely ascribed to the oxidation of α-farnesene, its physiology is not yet fully understood. To elucidate the mechanism of superficial scald development and possible means of prevention, we performed an integrated metabolite screen, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 82 publications
9
49
0
Order By: Relevance
“…The efficacy of 1-MCP was initially assigned to its role in reducing α-farnesene production by downregulating the expression of the α-farnesene synthase 1 gene (AFS1). However, recent findings 3,8 support that 1-MCP protects apples from developing scald not only by inhibiting ethylene-related physiological processes, but also by stimulating complex cold-acclimation reactions within the fruit. For instance, 1-MCP induced the expression of the sorbitol-6phosphate dehydrogenase 8 , a key element in the production of the cryoprotectant compound sorbitol 16 .…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…The efficacy of 1-MCP was initially assigned to its role in reducing α-farnesene production by downregulating the expression of the α-farnesene synthase 1 gene (AFS1). However, recent findings 3,8 support that 1-MCP protects apples from developing scald not only by inhibiting ethylene-related physiological processes, but also by stimulating complex cold-acclimation reactions within the fruit. For instance, 1-MCP induced the expression of the sorbitol-6phosphate dehydrogenase 8 , a key element in the production of the cryoprotectant compound sorbitol 16 .…”
Section: Introductionmentioning
confidence: 98%
“…Symptoms of superficial scald are consistent among most susceptible varieties of pome fruit, and shown as brown-dark patches on the fruit skin, resulting from the necrosis of the epidermis and hypodermal cortical tissues 1,3 . While the molecular and physiological mechanisms underlying scald in apples have been largely studied over the past few years 2,3,[6][7][8] , scarce information is available regarding this disorder in pears. The most accepted theory for scald development focuses on the auto-oxidation of the acylic sesquiterpene α-farnesene into conjugate trienols (CTols), which leads to the production and release of the ketone 6methyl-5-hepten-2-one 4,[9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that in addition to reduced ethylene and α-farnesene production, 1-MCP also reduced the accumulation of reactive oxygen species (ROS) in fruit peel, probably by promoting cell-membrane integrity 6 . Further studies revealed that 1-MCP stimulates the production of ROS scavengers, synthesis of fatty acids that could stabilize plastid and vacuole membranes against cold, and the accumulation of sorbitol that can act as a cryoprotectant 7 . In the proposed model, ROS production in response to cold stress plays a central role in scald development by disrupting membrane integrity and promoting the accumulation of phenolic compounds.…”
mentioning
confidence: 99%
“…Although superficial scald was intensively studied for several years, its molecular or biochemical determinism was mainly analysed after long time cold storage during symptom development 3,9 , or under 1-MCP or DPA treatments 4,7,8,[10][11][12] . Thus, early determinisms linked to the pre-harvest conditions, in particular to climate or fruit maturity stages remain poorly understood.…”
mentioning
confidence: 99%